A cooperativa C. Vale e as perspectivas dos produtores integrados à agroindústria em Palotina - PR - Belusso, Diane (2007)
The present paper identifies the reasons that have impelled the agricultural cooperatives of Paraná, particularly, 'C.Vale Cooperativa Agroindustrial', to implant agribusinesses industries, thus breaking with its original function of just receiving and trading raw materials on behalf of the cooperative members or associates. It situates the cooperativist company as a contradiction between theory and practice in cooperativism. It states that the presence of industries, in great cooperatives, was and still is permeated by actions from the federal government, besides the law institution that defines the national policies in relation to cooperativism, and which reated the juridical regime of such associations. It characterizes the space of agriculture in the West of Paraná, specifically in Palotina, with prominence to the decisive function of C.Vale, when transforming part of their associates into producers integrated into agribusiness. It verifies the relationship between C.Vale Cooperative and the integrated producers, as well as the rights and duties of both parts, starting from the integration contract or partnership, and also checking the dependence or independence level in relation to the industry. It understands the hybrid role of C.Vale Cooperative, in the sense of maintaining a parallel relationship among free and integrated producers, verifying, among the amount of social relationships, the contradictions then generated. It considers that the insertion of cooperatives in an agroindustrial cooperative net, echoes in the control of the agricultural production, in the evolution of the association model of rural producers, and also, in the social relationships of production.